সমাজ রাজনীতির এক দশক, ২০০০-২০০৯ - শাহনাওয়াজ, এ কে এম (ঢাকা : নভেল পাবলিশিং, 2011)
Articles chiefly on contemporary political issues of Bangladesh; includes articles on social condition of Bangladesh.
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-; Bangladesh -- Social conditions -- 21st century